2015
DOI: 10.1111/bph.13085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the novel BK (KCa1.1) channel opener GoSloSR‐5‐130 are dependent on the presence of BKβ subunits

Abstract: BACKGROUND AND PURPOSEGoSlo-SR compounds are efficacious BK (KCa1.1) channel openers, but little is known about their mechanism of action or effect on bladder contractility. We examined the effects of two closely related compounds on BK currents and bladder contractions. EXPERIMENTAL APPROACHA combination of electrophysiology, molecular biology and synthetic chemistry was used to examine the effects of two novel channel agonists on BK channels from bladder smooth muscle cells and in HEK cells expressing BKα al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…Additionally, HBD2 (human β-defensin 2) could activate BK channels via interactions with Leu41 and Gln43 of the β1 extracellular loop (Liu et al, 2013). A recent report showed that the newly identified BK channel opener GoSlo-SR-5-130, but not its analogue GoSlo-SR-5-6, required the presence of β1 or β4 subunit to achieve its the maximal modulatory effects on BK channels (Large et al, 2015). …”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…Additionally, HBD2 (human β-defensin 2) could activate BK channels via interactions with Leu41 and Gln43 of the β1 extracellular loop (Liu et al, 2013). A recent report showed that the newly identified BK channel opener GoSlo-SR-5-130, but not its analogue GoSlo-SR-5-6, required the presence of β1 or β4 subunit to achieve its the maximal modulatory effects on BK channels (Large et al, 2015). …”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…GoSlo-SR-5-6 (GoSlo) (10 μM) shifted the voltage dependence of activation in excess of −100 mV. Although the structure-activity relationships of these compounds has been established (31,32), little is known about their mode of action on BK channels, other than GoSlo does not require the β 1 -subunit to mediate its effects (33).…”
Section: +mentioning
confidence: 99%
“…Although GoSlo‐SR compounds reliably activate BK channels in electrophysiological experiments, their effects on the contractility of intact smooth muscle tissues appear variable. Thus, Large et al () showed that GoSlo‐SR‐5‐130 decreased rabbit bladder spontaneous contractility but did not alter contractions in response to electrical field stimulation or carbachol application. In contrast, the closely related compound, GoSlo‐SR‐5‐6 failed to alter bladder contractility (Large et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a more efficacious family of BK channel openers called the GoSlo‐SR compounds have been developed (Roy et al, ; Roy et al, ). The efficacy of some of them has been reported to depend on the presence of BK channel regulatory β and γ‐subunits (Kshatri et al, ; Large et al, ; Webb et al, ). These compounds, in particular GoSlo‐SR‐5‐130 and GoSlo‐SR‐5‐6,activated BK channels in freshly isolated smooth muscle cells from rabbit bladder (Large et al, ), rabbit corpus cavernosum (Hannigan et al, ), and bronchial smooth muscle (Bradley et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation